Chimeric crRNAs with 19 DNA residues in the guide region show the retained DNA cleavage activity of Cas9 with potential to improve the specificity - Kim, Hyo Young; Kang, Seong Jae; Jeon, Yongmoon; An, Jinsu; Park, Jihyun; Lee, Hee Jae; Jang, Jeong-Eun; Ahn, JongSeong; Bang, Duhee; Chung, Hak Suk; Jeong, Cherlhyun; Ahn, Dae-Ro (ROYAL SOC CHEMISTRY, 2019)
We demonstrated that 19 out of 20 RNA residues in the guide region of crRNA can be replaced with DNA residues with high GC-contents. The cellular activity of the chimeric crRNAs to disrupt the target gene was comparable to that of the native crRNA.